A highly diastereoselective [3+3] annulation reaction of aza-oxyallyl cations and nitrones. Issue 20 (16th May 2018) - Chen, Rongxing; Sun, Shaofa; Wang, Gangqiang; Guo, Haibing
Graphical abstract: Highlights: Excellent diastereo-control. Broad substrate scope. High chemical yield. Abstract: An efficient synthesis of 1, 2, 4-oxadiazinan-5-ones via [3+3] cycloaddition of in situ generated aza-oxyallyl cations with nitrones has been developed. The protocol features easy operation, excellent yields, excellent diastereo-control, broad substrate scope and good functional group tolerance.